Keys to Galatians: collected essays - Murphy-O'Connor, J. (A Michael Glazier Book, 2012)
Missions in Galatia, Macedonia, and Achaia before the Jerusalem Conference -- Paul in Arabia (Gal 1:17) -- The names for Jerusalem in Galatians (1:17-18; 4:25-26) -- To run in vain (Gal 2:2) -- Nationalism and church policy: reflections on Galatians 2:9 -- Galatians 2:15-16a: whose common ground? -- The irrevocable will (Gal 3:15) -- Galatians 4:13-14 and the recipients of Galatians -- The unwritten law of Christ (Gal 6:2) -- The origins of Paul's Christology: from Thessalonians to Galatians